2007
DOI: 10.1016/j.neuroscience.2006.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic neurons in medullary nuclei are among the post-synaptic targets of descending projections from infralimbic area 25 of the rat medial prefrontal cortex

Abstract: The medial prefrontal cortex (mPFC) is directly involved in the integration of cognitive and autonomic functions underlying flexible goal-directed behavior (Cechetto and Saper, 1990;Neafsey et al., 1993;Loewy, 1991;Owens et al., 1999;Van Eden and Buijs, 2000;Drevets, 2000;Heidbreder and Groenewegen, 2003). In the rat, the mPFC is composed of the anterior cingulate (ACd, Brodmann area 24b), prelimbic (PL, area 32), infralimbic (IL, area 25), and peduncular (P) cortices (Neafsey et al., 1993;Gabbott et al., 2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Labeling results from missed injections in our study confirmed this by producing little to no retrograde labeling within the PVN or other forebrain regions of interest when the FG injection site targeted structures situated dorsal (i.e., gracile or cuneate nuclei) or ventral (i.e., hypoglossal nucleus) to the mid-NST/DMV. Conversely, FG tracer injections centered within the mid-NST/DMV produced retrograde labeling in regions previously reported to project to the DVC (Gray and Magnuson, 1987, Danielsen et al, 1989, Rinaman, 2003b, Gabbott et al, 2007), including the mPFC (prelimbic and infralimbic cortices), CeA (primarily its lateral region), PVN (primarily its ventral parvicellular subdivision; see Fig. 8), and BNST (primarily its dorsolateral region; see Fig.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Labeling results from missed injections in our study confirmed this by producing little to no retrograde labeling within the PVN or other forebrain regions of interest when the FG injection site targeted structures situated dorsal (i.e., gracile or cuneate nuclei) or ventral (i.e., hypoglossal nucleus) to the mid-NST/DMV. Conversely, FG tracer injections centered within the mid-NST/DMV produced retrograde labeling in regions previously reported to project to the DVC (Gray and Magnuson, 1987, Danielsen et al, 1989, Rinaman, 2003b, Gabbott et al, 2007), including the mPFC (prelimbic and infralimbic cortices), CeA (primarily its lateral region), PVN (primarily its ventral parvicellular subdivision; see Fig. 8), and BNST (primarily its dorsolateral region; see Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Tracer injection sites targeted the mid-NST/DMV and were intentionally large in order to maximize the amount of retrograde labeling achieved. Previous reports have demonstrated that the PVN, BNST, CeA, and mPFC provide little or no direct input to hindbrain regions immediately surrounding the DVC (Luiten et al, 1985, Saha et al, 2000, Dong et al, 2001, Gabbott et al, 2007). Labeling results from missed injections in our study confirmed this by producing little to no retrograde labeling within the PVN or other forebrain regions of interest when the FG injection site targeted structures situated dorsal (i.e., gracile or cuneate nuclei) or ventral (i.e., hypoglossal nucleus) to the mid-NST/DMV.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the viscerosensory nucleus of the solitary tract (NTS) projects directly to the behavioral state system (23,24), the PTA/PVTa, and the ILA (Fig. 2), the latter two of which are noradrenergic (25,26). Aside from the pharmacological evidence of a central noradrenergic influence on stress, depression, and appetite (27), this is interesting because the ILA projects directly to the NTS, providing the substrate for a possible very long cortico > NTS feedback loop (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, each subregion has different inputs and outputs (Gabbott et al 2007; Hoover and Vertes 2007; Vertes et al 2015; Kuramoto et al 2016) and has different functional roles (Heidbreder and Groenewegen 2003; Kesner and Churchwell 2011; Vertes et al 2015). In particular, ACC and PrL play a role in attention and working memory, while the more ventral IL has been implicated in goal-directed behavior and autonomic functions (Miller and Cohen 2001; Heidbreder and Groenewegen 2003; Seamans et al 2008; Kesner and Churchwell 2011; Euston et al 2012; Parnaudeau et al 2013).…”
mentioning
confidence: 99%